Corporate Governance Propagation through Overlapping Directors - Bouwman, Christa H. S. (Review of Financial Studies, 2011)
How are governance practices propagated across firms? This article proposes, and empirically verifies, that observed governance practices are partly the outcome of network effects among firms with common directors. While firms attempt to select directors whose other directorships are at firms with similar governance practices (“familiarity effect”), this matching of governance practices is imperfect because other factors also affect the director choice. This generates an “influence effect” as directors acquainted with different practices at other firms influence the firm's governance to move toward the practices of those other firms. These network effects cause governance practices to converge.